2015
DOI: 10.1371/journal.pone.0117166
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Pharmacological and Psychological Interventions for the Treatment of Psychosis and Schizophrenia in Children, Adolescents and Young Adults: A Systematic Review and Meta-Analysis

Abstract: BackgroundStudies report contrasting results regarding the efficacy and safety of pharmacological, psychological, and combined interventions in psychosis and schizophrenia in children, adolescents and young adults.MethodsSystematic review and meta-analysis. Embase, Medline, PreMedline, PsycINFO, and CENTRAL were searched to July 2013 without restriction to publication status. Randomised trials comparing any pharmacological, psychological, or combined intervention for psychosis and schizophrenia in children, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 55 publications
0
71
0
2
Order By: Relevance
“…AP can be divided in two groups: first generation (typical) antipsychotics (FGA) and second-generation (atypical) antipsychotics (SGA) [2, 3]. Efficacy of AP in youth has been demonstrated for psychotic symptoms [4], bipolar disorder [5], irritability in autistic children [6], tics [7], and some forms of (severe) aggressive behaviour [8, 9]. Ample use of AP drugs has been described in children with a mental handicap and behavioral symptoms [10].…”
Section: Introductionmentioning
confidence: 99%
“…AP can be divided in two groups: first generation (typical) antipsychotics (FGA) and second-generation (atypical) antipsychotics (SGA) [2, 3]. Efficacy of AP in youth has been demonstrated for psychotic symptoms [4], bipolar disorder [5], irritability in autistic children [6], tics [7], and some forms of (severe) aggressive behaviour [8, 9]. Ample use of AP drugs has been described in children with a mental handicap and behavioral symptoms [10].…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that the combination of family interventions with individual CBT can be strongly effective in extending the time-to-relapse in young people with psychosis. 56 It has also been argued that CBT may be effective in the treatment of schizophrenia but that it may not outperform other therapy alternatives when addressing several outcomes such as adverse effects, relapse, rehospitalization, global mental state and social functioning. 57 Orfanos et al 58 found no specific effects of CBT group interventions on the negative symptoms and social functioning of patients with schizophrenia.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Minimizing the use of antipsychotics for individuals with ARMS is preferable because the use of antipsychotics may induce health problems and brain volume reduction (Ho et al, 2011). Further, the risk-benefit ratio of antipsychotics for the young population may be relatively low compared to the adult population (Stafford et al, 2015). Excessive use of antipsychotics for ARMS and overdiagnosis of schizophrenia is matter of great concern in Japan, and probably also in many other areas, with the exception of a limited number of Western regions (Katsura et al, 2014;Mizuno, Nemoto, Tsujino, Funatogawa, & Takeshi, 2012).…”
Section: Discussionmentioning
confidence: 99%